2020
DOI: 10.1016/j.ymthe.2019.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Single SERCA2a Therapy Ameliorated Dilated Cardiomyopathy for 18 Months in a Mouse Model of Duchenne Muscular Dystrophy

Abstract: Loss of dystrophin leads to Duchenne muscular dystrophy (DMD). A pathogenic feature of DMD is the significant elevation of cytosolic calcium. Supraphysiological calcium triggers protein degradation, membrane damage, and eventually muscle death and dysfunction. Sarcoplasmic/endoplasmic reticulum (SR) calcium ATPase (SERCA) is a calcium pump that transports cytosolic calcium to the SR during excitationcontraction coupling. We hypothesize that a single systemic delivery of SERCA2a with adeno-associated virus (AAV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 59 publications
5
39
0
1
Order By: Relevance
“…This finding is in line with abnormally elevated sarcolipin levels in the muscle of DMD patients and mouse models of the disease ( Voit et al, 2017 ). Most interestingly in this context, in recent studies, both a single systemic delivery of SERCA2a with adeno-associated virus ( Wasala et al, 2020 ) and sarcolipin deletion ( Voit et al, 2017 ) improved Ca 2+ recycling and provided considerable benefits in mouse models of DMD.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with abnormally elevated sarcolipin levels in the muscle of DMD patients and mouse models of the disease ( Voit et al, 2017 ). Most interestingly in this context, in recent studies, both a single systemic delivery of SERCA2a with adeno-associated virus ( Wasala et al, 2020 ) and sarcolipin deletion ( Voit et al, 2017 ) improved Ca 2+ recycling and provided considerable benefits in mouse models of DMD.…”
Section: Discussionmentioning
confidence: 99%
“…SERCA activity can be reduced through several mechanisms, including (i) down-regulation of SERCA expression, (ii) posttranslational modification of SERCA protein, and (iii) differential expression and function of SERCA regulators. In the dystrophic myocardium of mouse models and human patients, SERCA2a levels remain unchanged (Voit et al, 2017;Wasala et al, 2020). In the mdx mouse, SERCA1a expression is increased in the spared intrinsic laryngeal and toe muscles but is reduced in the EDL muscle (Dowling et al, 2003;Ferretti et al, 2009).…”
Section: Role Of Serca and Its Regulatorsmentioning
confidence: 99%
“…Irrespective of SERCA levels, SR Ca 2+ uptake is significantly reduced in dystrophin-deficient cardiac and skeletal muscles, indicating decreased SERCA function (Schneider et al, 2013;Voit et al, 2017;Wasala et al, 2020;Mareedu et al, 2021). Oxidative posttranslational modification has been shown to play an important role in SERCA activity in non-dystrophic heart diseases (Lancel et al, 2010;Horakova et al, 2013).…”
Section: Role Of Serca and Its Regulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported the beneficial effects of neonatal AAV2/6-SERCA1a overexpression in the diaphragm [ 129 ] as well as cardiac improvements after AAV9-SERCA2a delivery to 12-month-old mdx mice (1 × 10 12 vg particles/mice) [ 130 ]. Long-lasting effects of such therapy were studied by Wasala et al [ 131 ], and the amelioration of cardiomyopathy and skeletal muscle protection was demonstrated after 18 months after a single systemic delivery of SERCA2a isoform (AAV9-SERCA2a; 6 × 10 12 vg particles/3-month-old mdx mouse). SERCA2 was highly overexpressed in the heart and skeletal muscle causing an increase in SR calcium uptake, better physical performance, no signs of myocardial fibrosis, and the improvement in ECG and restoration of ejection fraction in treated dystrophic animals.…”
Section: Gene-based Therapiesmentioning
confidence: 99%